Colour Vision Model-Based Approach for Segmentation of Traffic Signs. (7th February 2008) - Gao, Xiaohong; Hong, Kunbin; Passmore, Peter; Podladchikova, Lubov; Shaposhnikov, Dmitry
Abstract : This paper presents a new approach to segment traffic signs from the rest of a scene via CIECAM, a colour appearance model. This approach not only takes CIECAM into practical application for the first time since it was standardised in 1998, but also introduces a new way of segmenting traffic signs in order to improve the accuracy of colour-based approach. Comparison with the other CIE spaces, including CIELUV and CIELAB, and RGB colour space is also carried out. The results show that CIECAM performs better than the other three spaces with 94%, 90%, and 85% accurate rates for sunny, cloudy, and rainy days, respectively. The results also confirm that CIECAM does predict the colour appearance similar to average observers.